South Sudan's newest war: when two old men divide a nation - Koos, Carlo; Gutschke, Thea (2014)
Abstract: A political power struggle between South Sudanese president Salva Kiir and former vice president Riek Machar resulted in violent clashes between ethnic army factions in December 2013. Since then fighting has spread across South Sudan and claimed the lives of around 10,000 people. South Sudan has experienced several insurgencies since gaining independence in 2011. Nevertheless, the current war has the potential to be more destructive to the country than previous ones because both parties - President Salva Kiir, an ethnic Dinka, and his opponent, former vice president Riek Machar, an ethnic Nuer - are instrumentalizing ethnic identities and pulling their communities into their personal feud. A number of latent issues have contributed to the current crisis. These include South Sudan's dysfunctional political system and inadequate political leadership, the historical distrust between the Dinka and the Nuer, and the country's unhealthy dependence on oil rents. The civilian population is